2019
DOI: 10.1055/s-0039-1700547
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Pneumoperitoneum Effects on Molecular Markers of Tumor Invasiveness in SH-SY5Y Neuroblastoma Cells

Abstract: Introduction CO2 pneumoperitoneum can influence the biological behavior of neuroblastoma (NB). Angiogenesis and genetic features are responsible for malignant phenotype of this tumor. We examined the CO2 effects on N-Myc, vascular endothelial growth factor (VEGF), and matrix metalloproteinase-2 (MMP-2) expression as critical biomarkers of tumor invasiveness, in NB cells without N-Myc amplification. Materials and Methods SH-SY5Y cells were exposed to CO2 (100%) at 15 mm Hg pressure for 4 hours and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Several studies have highlighted how hypoxemia and a lower pH could improve angiogenesis and Myc (dedifferentiating factor and negative prognostic marker) over-expression in NBs cells [55]. On the other hand, Montalto et al [56] demonstrated how, despite an initial increase of HIF-1 alpha and Myc expression after CO2 exposal, they returned at a basal level after 24 h of standard condition. Further studies should clarify whether CO2 exposure, and therefore MIS, plays a role in tumors growth and metastasis process, influencing the patient's prognosis.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…Several studies have highlighted how hypoxemia and a lower pH could improve angiogenesis and Myc (dedifferentiating factor and negative prognostic marker) over-expression in NBs cells [55]. On the other hand, Montalto et al [56] demonstrated how, despite an initial increase of HIF-1 alpha and Myc expression after CO2 exposal, they returned at a basal level after 24 h of standard condition. Further studies should clarify whether CO2 exposure, and therefore MIS, plays a role in tumors growth and metastasis process, influencing the patient's prognosis.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%